Peningkatan Kinerja K3 Dan KO Di Perusahaan Pertambangan Melalui Penerapan SMKP - Nurul Kamal; Mirna Rahmah Lubis; Muhammad Jehan (Jurnal Teknik Mesin Unsyiah, 2019)
PT Adaro Indonesia is a mining company that operates under the covenant of works concessions of coal mining, on the mining area of PT Adaro Indonesia or ADMO (Adaro Mining Operation) there is a mining services company PT Saptaindra Sejati (PT. SIS), that move in modern mining and contractors provide services for mining and related industries in the ADMO. The research methodology was literature study, field observation, and questioning employees. PT.SIS has been applied Mining Safety Management System application of Mineral and Coal as know as (SMKP Minerba) for all elements, but the level of the achievement on the elements are 88.29% still dropping from the previous year to reach 92.80%. this publication only for element IV, Implementation. The achievement on this element only reached 79% below previous year reach 91%. Provide recommendations as an attempt to improvement efforts to PT. SIS, as well as the company's internal evaluation in order to no longer obtained the findings of major or minor in following (SMKP) audit.